Do probiotics modulate dietary intake? Pilot data from a randomized controlled sub-study of the ProBioHRV clinical trial in patients with depression and healthy controls - Julia Corinna Putz; Marilena Wilding; Sonja Lackner; Martin Narrath; Daria Schlotmann; Marie-Therese Sallmutter; Jasmin Tatzer; Andreas Brandstätter; Julia Deborah Lang; Sandra Holasek; Julian Wenninger; Mary I. Butler; et al. (PLoS ONE, 2026)
Background The gut microbiome plays a central role in human health and is strongly influenced by diet. Probiotics can beneficially modulate the microbiome and, through the gut–brain axis, may affect mood, appetite, and food preferences. This randomized controlled trial examined whether three months of probiotic supplementation could alter dietary intake in individuals with major depression ( MD ) and healthy controls ( HC ). Methods In this double-blind, placebo-controlled trial, 53 participants (23 with MD , 30 HC ) received either a multi-strain probiotic or placebo twice daily for three months. Dietary intake was assessed at baseline and three follow-ups using the Vienna Food Record (VFR). Nutritional data were analyzed with nut.s® software and evaluated using mixed ANOVAs for repeated measures. These analyses represent additional data collected within the framework of the ProBioHRV study. Results Changes across dietary measures were generally small, with only a limited number reaching statistical significance. Significant three-way interactions ( time × intervention × diagnosis ) emerged for vitamin D intake, dietary variety, folic acid, and diversity. In HC , probiotic supplementation was associated with higher vitamin D intake after one week, while in MD , a similar increase was observed after three months (trend level, p = .058). Conversely, participants receiving probiotics showed lower dietary variety and diversity scores at several time points. Across all time points, folic acid intake was lower in MD compared to HC , independent of intervention. Conclusion Probiotic supplementation did not produce consistent changes in nutrient intake but showed exploratory, time- and group-dependent patterns for selected measures, including vitamin D intake and dietary variety and diversity. Given the pilot nature of the study, these findings are descriptive and hypothesis- generating. Larger, well-powered studies with objective nutritional and microbiome measures are required.